2014
DOI: 10.1016/j.jaci.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal rhinovirus induces mucous metaplasia and airways hyperresponsiveness through IL-25 and type 2 innate lymphoid cells

Abstract: Background Early-life human rhinovirus (RV) infection has been linked to asthma development in high risk infants and children. Nevertheless, the role of RV infection in the initiation of asthma remains unclear. Objective We hypothesized that, in contrast to infection of mature BALB/c mice, neonatal infection with RV promotes an IL-25-driven type 2 response which causes persistent mucous metaplasia and airway hyperresponsiveness. Methods Six day-old and eight week-old BALB/c mice were inoculated with sham H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
159
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 52 publications
9
159
0
1
Order By: Relevance
“…In our previous report, we found that RV infection of neonatal mice induced mucous metaplasia and airways hyperresponsiveness, which was dependent on the type 2 cytokine IL-13 (12,13). In this study, we hypothesized that IFN-g counteracts the observed asthma phenotype.…”
Section: Ifn-g Reduces Mucous Metaplasia In Rv-infected Neonatal Micementioning
confidence: 79%
See 2 more Smart Citations
“…In our previous report, we found that RV infection of neonatal mice induced mucous metaplasia and airways hyperresponsiveness, which was dependent on the type 2 cytokine IL-13 (12,13). In this study, we hypothesized that IFN-g counteracts the observed asthma phenotype.…”
Section: Ifn-g Reduces Mucous Metaplasia In Rv-infected Neonatal Micementioning
confidence: 79%
“…Neonatal T cells and monocytes demonstrate deficient IFN-g production (14)(15)(16), as well as diminished responses to IFN-g stimulation (17,18). Accordingly, we found that IFN-g production was suppressed in RV-infected immature 6-day-old mice in comparison with 21-day-old and mature 8-week-old mice (13). Infants with reduced blood mononuclear cell production of IFN-g, the principal type 1 cytokine, have been shown to be at a greater risk of recurrent virus-induced wheezing and asthma development (19)(20)(21)(22).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, despite strong epidemiological evidence supporting the role of RV in the pathogenesis of asthma, airway reactivity and airflow limitation, the underlying mechanisms are unclear. Although damage to the developing airways and altered immune responses are thought to be the main mechanisms through which RV could induce asthma and airway hyperreactivity later in life [107,108], others have suggested that early-life infection with RV might be the first indication of the pre-existing tendency in some children to develop asthma, including among preterm infants [109,110]. The ability of RV to induce prolonged and exaggerated inflammatory responses after the initial infection has been described as a potential contributor to the development of chronic respiratory morbidity among preterm infants, with limited data demonstrating increased airway secretion of inflammatory cytokines and remodelling molecules during acute RV infection, particularly among those with BPD [108,111].…”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…R ecent studies have highlighted the role of innate immune cells including pulmonary macrophages in more severe types of asthma, which are often associated with steroidresistant airway hyperresponsiveness (AHR) (1,2). Acute exacerbations of asthma, often triggered by respiratory bacterial or viral infections, are critical clinical problems for asthma management and treatment.…”
mentioning
confidence: 99%